2008
DOI: 10.1016/j.fertnstert.2007.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in self-reported infertility and risk factors for infertility in a cohort of black and white women: The CARDIA Women's Study

Abstract: Objective-To determine racial differences in self-reported infertility and in risk factors for infertility in a cohort of black and white women.Design-A cross-sectional analyses of data from the longitudinal Coronary Artery Risk Development in Young Adults (CARDIA) Study, a prospective, epidemiologic investigation of the determinants and evolution of cardiovascular risk factors among black and white young adults and from the ancillary CARDIA Women's Study (CWS).Setting-Population-based sample from 4 US communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 44 publications
1
62
1
Order By: Relevance
“…A recent report from the Coronary Artery Risk Development in Young Adults (CARDIA) study indicates that among non-surgically sterile women, African American women had a twofold increase in odds of reporting a history of infertility (9). Financial barriers limit access to diagnosis, evaluation, and treatment and may lead to selectively underestimating the frequency of infertility in the same population groups (10).…”
Section: Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…A recent report from the Coronary Artery Risk Development in Young Adults (CARDIA) study indicates that among non-surgically sterile women, African American women had a twofold increase in odds of reporting a history of infertility (9). Financial barriers limit access to diagnosis, evaluation, and treatment and may lead to selectively underestimating the frequency of infertility in the same population groups (10).…”
Section: Prevalencementioning
confidence: 99%
“…Because the global focus of public health policies and programs has justifiably been on containing population growth and providing affordable, safe, and effective family planning services, the inability to procreate has not traditionally made it to the top of the priority list in many developing nations. The * To compute a preliminary estimate of these costs, we used the annual numbers of infertility visits and non-ART treatment procedures estimated by the NSFG, the annual number of male infertility visits and ambulatory surgery visits for varicocele estimated by Meacham et al (9), and the number of ART cycles registered in the NASS, the average costs per non-ART infertility treatment procedure reported in a large commercial database (Medstat; Thomson Reuters, New York, NY), and the estimate of the cost for ART cycles published by the ASRM. We also assumed that the number and distribution of term and preterm live-born infants were the same for ART and non-ART infertility treatment and applied the total medical care costs during the first 5 years of life associated with preterm and non-preterm live-born children estimated by the Institute of Medicine (40).…”
Section: Infertility As a Global Issuementioning
confidence: 99%
“…Human data, though incomplete, does suggest that darker-skinned people, especially at higher latitudes, have greater occurrence of infertility [38][39][40][41][42] . However, few studies have linked this infertility to low vitamin D levels; rather, there has been an emphasis on socioeconomic factors and stress that might be contributing to this phenomenon [ 43,44 ] . Unfortunately, there are no migrant studies where sun re fl ectance/vitamin D exposure and indices of fertility were measured at the equator and similar indices of fertility measured in a similar racial/ethnic population at a higher latitude.…”
Section: Implantation/fertilitymentioning
confidence: 99%
“…It was hypothesized that Black and Hispanic women would demonstrate higher scores on the overall Risk for Infertility scale, given that they are the most likely experience infertility (Bell, 2014;Wellons et al, 2008;Greil et al, 2011). However, the composite measure of Risk for Infertility assembled in the current study did not show this effect;…”
Section: Risk For Infertility As Function Of Sexual Identity Sexual mentioning
confidence: 55%
“…Researchers analyzing data from the 1982-2002 United States National Surveys of Family Growth (NSFG) found that rates of infertility (as defined by the inability to conceive after 12 months of intercourse, or by way of other physical barriers to fertility) were much higher among Black women (at 20%) and Hispanic women (at 18%) than among White/Caucasian women (at 7%) (Bitler & Schmidt, 2006). Another study found that Black women in four population-based samples in the U.S. were twice as likely to experience infertility compared to their White RISK FOR INFERTILITY AS FUNCTION OF SEXUAL IDENTITY, SEXUAL BEHAVIOR, AND RACE AMONG U.S. WOMEN 8 counterparts (Wellons et al, 2008). While there is no consensus as to the exact rates of infertility among women in the U.S. as a function of race, researchers are in agreement that non-White women are more likely than others to experience infertility (Greil et al, 2016).…”
Section: Disparities In Infertilitymentioning
confidence: 99%